Word Formation Theories of Halle and Aronoff and Persian Lexicon - محمد امین صراحی (مطالعات زبانی و بلاغی)
This study aims at analyzing Persian lexicon based on the morpheme-based morphological theory of Halle and the word-based theory of Aronoff. In doing so, the researchers make use of the morphological behavior of some Persian verb roots in derivation, interjections manner of derivation, and the overgenerativeness of some Persian affixes. The results of this study show that the morpheme-based theory of Halle, on the one hand, does not suit Persian lexicon. On the other hand, though more appropriate, the word formation rules of the theory of Aronoff fails to explain some word formation processes in Persian.